Cardiorenal protection with SGLT2 inhibitors in patients with diabetes mellitus: from biomarkers to clinical outcomes in heart failure and diabetic kidney disease - Liu, Hongyan; Sridhar, Vikas S.; Boulet, Jacinthe; Dharia, Atit; Khan, Abid; Lawler, Patrick R.; Cherney, David Z.I. (Metabolism, clinical and experimental, 2022)
Type 2 diabetes (T2D) is one of the most common causes of chronic kidney disease (CKD) and cardiovascular (CV) disease. Until recently, glycemic and BP control were the cornerstones for preventing progression of CKD and CV disease associated with T2D. However, there has been a paradigm shift in treatment since the publication of the first clinical trial demonstrating benefits of sodium glucose cotransporter 2 (SGLT2) inhibitors in 2015. SGLT2 inhibitors have been shown to reduce the risk of major adverse CV events and progression of kidney disease in the setting of T2D. However, the elucidation of mechanisms of underlying these clinical benefits is the subject of ongoing investigation. Experimental studies have shown that SGLT2 inhibitors have diverse pleiotropic effects such as modulation of neurohormones such as the renin-angiotensin-aldosterone system, increasing hematocrit, altering energy substrate use, and attenuating systemic inflammation and oxidative stress, all of which have been implicated in the CV and kidney protective effects of SGLT2 inhibitors. In this review, we highlight biomarkers linked with diabetic kidney disease and heart failure and discuss how SGLT2 inhibitor-associated changes potentially mediate the cardiorenal protection observed with these therapies. •SGLT2 inhibitors, biomarkers, and clinical outcomes in heart and kidney disease•SGLT2 inhibitors have various cardiovascular and kidney protective effects.•Biomarker analyses elucidate potential mechanisms behind SGLT2 inhibitor benefits.•SGLT2 inhibitors modulate neurohormones and restore tubuloglomerular feedback.•Increased hematocrit and attenuation of inflammation after SGLT2 inhibition